PENALTY AGAINST PHONE CREDIT HACKING THROUGH THE ‘ISI PULSA MASSAL.EXE’ APPLICATION - Rahmawati, Poppi; Priyati, Sri (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
Cyber crime is defined as a type of crime related to the misuse of information technology. The causes include unrestricted internet access, as well as negligence from users. In Indonesia, the increase in cyber attacks and data hacking cases in the past year according to the National Cyber Security Index report and Reboot Digital PR Service is the worst cybersecurity country in Asia with a cyber danger score of 82.5 out of 100.Using normative legal research using secondary data including laws, judicial decisions, legal theories. As well as with the Legislative Approach which is carried out by examining all relevant laws and regulations and the Case Approach which is carried out by examining cases related to the issues at hand and court decisions.Law Number 11 of 2008 concerning Electronic Information and Transactions or commonly called the ITE Law has special rules regarding the use of information technology, in the discussion of cybercrime. In hacking through artificial applications, especially hacking the credit balance of an individual can be subject to criminal sanctions, such as the case, two people from Wonosobo, Central Java named Abdul Aziz and Tahyan, have been caught by the Special Investigation Directorate team or Ditreskrimsus at the South Kalimantan Police (KalSel). Criminalization of credit balance hacking through artificial applications can be applied by. ionally, challenges such as a shortage of police personnel and insufficient public outreach on traffic law compliance contribute to the system's inefficiency.